ON ?-STATISTICAL CONVERGENCE OF ORDER ? OF SEQUENCES OF FUZZY NUMBERS - Altinok, Hifsi (World Scientific Publ Co Pte Ltd, 2012)
In this article we introduce the concepts of lambda-statistical convergence of order beta and strong. lambda p-summability of order beta for sequences of fuzzy numbers. Also, we establish some relations between the lambda-statistical convergence of order beta and strong lambda p-summability of order beta and present some interesting examples to show strictness of some inclusion relations.
Keywords: Fuzzy number; statistical convergence; Cesaro summability